2023
DOI: 10.3233/jad-221259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comorbidities on Ten-Year Survival in Patients with Dementia

Abstract: Background: There is a verified association between comorbidity and survival in patients with dementia. Objective: To describe the ten-year survival probability of patients with dementia and to identify the impact of comorbidity. Methods: The prognostic retrospective cohort study was conducted using data from adults with dementia who had visited the outpatient departments at Maharaj Nakorn Chiang Mai hospital between 2006 and 2012. Dementia was verified in accordance with standard practice guidelines. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Regarding H. pylori/Mets-related AF involvement in cerebral disorders, AF has been implicated in the progression from mild cognitive impairment (MCI) to dementia [89]. There is evidence connecting AF with an increased risk and mortality rate across all categories of dementias, such as vascular dementia and AD [90][91][92][93]. Catheter ablation in AF patients, beyond H. pylori eradication, appears to decrease the risk of dementia and AD [94]; AD is reduced in patients who have undergone AF catheter ablation [95].…”
Section: The Role Of H Pylori/mets-related Atrial Fibrillation Pathol...mentioning
confidence: 99%
“…Regarding H. pylori/Mets-related AF involvement in cerebral disorders, AF has been implicated in the progression from mild cognitive impairment (MCI) to dementia [89]. There is evidence connecting AF with an increased risk and mortality rate across all categories of dementias, such as vascular dementia and AD [90][91][92][93]. Catheter ablation in AF patients, beyond H. pylori eradication, appears to decrease the risk of dementia and AD [94]; AD is reduced in patients who have undergone AF catheter ablation [95].…”
Section: The Role Of H Pylori/mets-related Atrial Fibrillation Pathol...mentioning
confidence: 99%
“…In addition, advanced age, hospitalization for myocardial infarction, high serum sodium levels, lower Barthel index, and the incidence of complications during hospitalization have been identified as predictors for higher mortality in people with dementia [ 11 ]. Studies in Thailand have identified mortality risk factors in people with dementia [ 12 , 13 ]. However, specific factors associated with mortality after surviving unplanned hospitalization have not been reported in the available studies.…”
Section: Introductionmentioning
confidence: 99%